P53 expression and K-ras mutation in colorectal adenomas. Issue 5 (May 1993) - Scott, N; Bell, S M; Sagar, P; Blair, G E; Dixon, M F; Quirke, P
Abstract : The frequency of p53 overexpression and K-ras codon 12 mutation was investigated in a series of colorectal adenomas. p53 was detected by immunohistochemistry in only 5% of tumours, whereas K-ras mutation was found in eight of 30 adenomas examined. In vitro, mutant p53 and ras genes cooperate to transform primary rat cells into a tumourigenic cell line. The presence of both p53 overexpression and K-ras mutation in a benign tubulovillous polyp in the present series suggests that in vivo this combination of events is insufficient to cause malignant transformation of a large bowel adenoma.